The Feasibility Study of Moodle-Based E-Module to Increase The Numeration Literacy of Elementary School Students - Rio Samudra Pramono (DIDAKTIKA: Jurnal Pendidikan Sekolah Dasar, 2021)
Numeration literacy is an ability to formulate, and interpret mathematics in contexts variety, including the ability to reason mathematically using concepts, facts, procedures, as a tool to describe, predict, and explain an event or phenomenon. This research aims to determine the feasibility of moodle-based e-module to increase numeration literacy for elementary school students. This study uses the Research Development (RD) model from Borg Gall with ten development stages. Data collection technique using purposive sampling. The developed product was then validated by media expert, content expert, and learning expert by using instrument validation sheets that are tailored to each expert. The data on the feasibility of moodle-based e-module in the form of the percentage of e-module validity and notes from experts. The results of the feasibility of moodle-based e-module were analyzed descriptively. The result of this development research is a moodle-based e-module for 3rd grader elementary school students by media expert obtain a very feasible level of validity with a percentage of 100%, material expert obtains a proper validity level with a percentage of 71%, and learning expert with a very feasible level of validity with a percentage of 97%. These results show that the e-module developed is in the feasible criteria and can be implemented with a few revisions for the material.